Comparison of Application of Jigsaw IV and Reverse Jigsaw Methods based on Students’ Participation and Achievement - Komang Talita Putri Sri Dewati; Basori Basori; Agus Efendi (Journal of Informatics and Vocational Education, 2019)
The purpose of this research is to study the effects of Jigsaw IV and Reverse Jigsaw cooperative learning model from participation and achievement (cognitive abilities). The method used in this research was the experiment 2x2 factorial design. The population was students (X Class) of SMK N 3 Surakarta. This research used a cluster random sampling technique. The techniques of collecting data of this research were the interview, observation, questionnaire, and testing. The techniques of data analysis were used as a two-way analysis of variance. Based on this research, it could be concluded as follows: (1) there is a different influence between application of Jigsaw IV and Reverse Jigsaw cooperative learning model based on students' cognitive ability (Sig. = 0,045 < 0,05), (2) there is a different influence between the high and low category of students' participation toward cognitive ability (Sig. = 0,000 < 0,05), (3) there is an interaction between the influence of cooperative learning type Jigsaw IV and Reverse Jigsaw application and students' participation toward students' cognitive ability (Sig. = 0,027 < 0,05). The result of this research could be put into consideration for the teacher to application Jigsaw IV and Reverse Jigsaw cooperative learning model in the learning activity.